Analysis of the Marketing Strategy of Sharia Insurance Services in Increasing Customer Loyalty - Ratna Dewi (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aims to test and analyze the marketing strategy of Islamic insurance services in increasing customer loyalty at the Pru Barokah Agency office of PT. Makassar Prudential. The population in this study were agents (marketers) and customers in the city of Makassar with a total of 1204 agents and 4987 customers. The sampling technique used non-probability sampling. The number of samples used were 98 samples obtained from the slovin formulation. The type of data used is primary data collected by distributing questionnaires to all respondents. All hypotheses proposed in this study will be proven through the coefficient of determination test, partial test (t test) and simultaneous test (f test). The results of this study indicate that the marketing strategy which includes product, price, distribution and promotion is very influential on increasing sharia insurance customer loyalty at the Pru Barokah Agency office of PT Prudential Makassar. And the variable that has the most dominant influence is the product variable with the questionnaire count data that is distributed to determine the percentage of significant and dominant variable influence among other variables.